A Chronological Bibliography of Turkish Literature in English Translation: 2004 – 2020. Issue 1 (4th May 2021) - Horzum, Şafak; Ağın, Başak
Abstract : This bibliography, which covers English translations of literary works produced in Turkish—including the works penned by minorities living in Turkey—from 2004 to 2020, is a sequel to Saliha Paker and Melike Yılmaz's bibliographic research published in the 2004 special issue "Turkish Literature and Its Translation" of Translation Review (vol. 68, no. 1). Paker and Yılmaz's work, despite its comprehensive coverage from 1949 to 2004, leaves out the translations published in the latter half of the cut-off date, presumably due to the publication date of the issue. Therefore, the following chronological bibliography begins with the works that were not included in the previous study. Taking Paker and Yılmaz's research as its basis, this bibliography includes literary genres common to world literatures, such as poetry, drama, novel, short story, as well as creative non-fiction such as travel literature and memoir. Other works of non-fiction and self-published works are not represented here.